Responses of Fine Roots at Different Soil Depths to Different Thinning Intensities in a Secondary Forest in the Qinling Mountains, China - Pang, Yue; Tian, Jing; Yang, Hang; Zhang, Kai; Wang, Dexiang (Biology (Basel, Switzerland), 2022)
Fine roots make critical contributions to carbon stocks and terrestrial productivity, and fine roots with different diameters exhibit functional heterogeneity. However, the changed characteristics of fine roots with different diameters at different soil depths following thinning disturbances are poorly understood. We investigated the biomass, production, mortality and turnover rate of <0.5 mm, 0.5–1 mm, and 1–2 mm fine roots at 0–20 cm, 20–40 cm, and 40–60 cm soil depths under five thinning intensities (0%, 15%, 30%, 45%, and 60%) in a secondary forest in the Qinling Mountains. The biomass, production and turnover rate of <0.5 mm fine roots fluctuated with increasing thinning intensities, while the 0.5–1 mm and 1–2 mm fine-root biomass significantly decreased. The thinning intensities had no effects on the fine-root necromass or mortality. The change in the fine-root characteristics in deeper soils was more sensitive to the thinning intensities. The principal component analysis results showed that increased <0.5 mm fine-root biomass and production resulted from increased shrub and herb diversity and biomass and decreased soil nutrient availability, stand volume, and litter biomass, whereas the 0.5–1 mm and 1–2 mm fine-root biomass showed the opposite trends and changes. Our results suggest that different thinning intensities exhibit varied influential mechanisms on the changed characteristics of fine roots with different diameters.